T-LAK cell-originated protein kinase (TOPK): an emerging target for cancer-specific therapeutics. Issue 11 (November 2018) - Herbert, Katharine; Ashton, Thomas; Prevo, Remko; Pirovano, Giacomo; Higgins, Geoff
Abstract 'Targeted' or 'biological' cancer treatments rely on differential gene expression between normal tissue and cancer, and genetic changes that render tumour cells especially sensitive to the agent being applied. Problems exist with the application of many agents as a result of damage to local tissues, tumour evolution and treatment resistance, or through systemic toxicity. Hence, there is a therapeutic need to uncover specific clinical targets which enhance the efficacy of cancer treatment whilst minimising the risk to healthy tissues. T-LAK cell-originated protein kinase (TOPK) is a MAPKK-like kinase which plays a role in cell cycle regulation and mitotic progression. As a consequence, TOPK expression is minimal in differentiated cells, although its overexpression is a pathophysiological feature of many tumours. Hence, TOPK has garnered interest as a cancer-specific biomarker and biochemical target with the potential to enhance cancer therapy whilst causing minimal harm to normal tissues. Small molecule inhibitors of TOPK have produced encouraging results as a stand-alone treatment in vitro and in vivo, and are expected to advance into clinical trials in the near future. In this review, we present the current literature pertaining to TOPK as a potential clinical target and describe the progress made in uncovering its role in tumour development. Firstly, we describe the functional role of TOPK as a pro-oncogenic kinase, followed by a discussion of its potential as a target for the treatment of cancers with high-TOPK expression. Next, we provide an overview of the current preclinical progress in TOPK inhibitor discovery and development, with respect to future adaptation for clinical use.